HARDNESS and SURFACE ROUGHNESS of RELINE and DENTURE BASE ACRYLIC RESINS AFTER REPEATED DISINFECTION PROCEDURES - Machado, Ana Lucia [UNESP]; Breeding, Larry C.; Vergani, Carlos Eduardo [UNESP]; da Cruz Perez, Luciano Elias [UNESP] (Mosby-elsevier, 2009)
Statement of problem. Microwave irradiation and immersion in chemical solutions have been recommended for denture disinfection. However, the effect of these procedures on the surface characteristics of denture base and reline resins has not been completely evaluated.Purpose. The purpose of this study was to evaluate the effect of microwave and chemical disinfection on the Vickers hardness (VHN) and surface roughness (Ra, mu m) of 2 hard chairside reline resins (Kooliner, DuraLiner II), and 1 heat-polymerizing denture base resin (Lucitone 550).Material and methods. Specimens (12 x 12 x 3 mm) were divided into 2 control and 4 test groups (n=8). Hardness and roughness measurements were performed after: polymerization and immersion in water (37 degrees C) for 7 days (controls), or repeated exposure to disinfection by Immersion In sodium perborate (50 degrees C/10 min) or microwave irradiation (650 W/6 min). Measurements of surface roughness (Ra, mu m) and hardness (kg/mm(2)) were analyzed using 3-way ANOVA and Tukey's Honestly Significant Difference (HSD) test (alpha=.05).Results. Microwave and chemical disinfection increased the mean (SD) hardness of Kooliner (from 4.1 to 7.5 kg/mm(2)) and DuraLiner II (from 2.6 to 5.6 kg/mm(2)), whereas Lucitone 550 (14.4 kg/mm(2)) remained unaffected. Disinfection by immersion in sodium perborate increased the surface roughness of DuraLiner II (from 0.13 to 0.26 mu m) and Kooliner (from 0.16 to 0.26 mu m), regardless of the number of cycles. For Lucitone 550, an increase in roughness was observed after 2 cycles of chemical disinfection (from 0.12 to 0.26 mu m). Two cycles of microwave disinfection increased the roughness of both reline resins (DuraLiner II: from 0.13 to 0.22 mu m; Kooliner: from 0.16 to 0.24 mu m), whereas repeated microwave disinfection increased the roughness of DuraLiner II (from 0.11 to 0.25 mu m).Conclusions. Disinfection by immersion in sodium perborate or microwave irradiation did not adversely affect the hardness of all materials evaluated. The effect of both disinfection methods on the roughness varied among materials. (J Prosthet Dent 2009;102:115-122)